Dilemmas and Paradoxes of English Language-and-Culture Teaching: Foreign or International? - Konieczna, Anna (Glottodidactica, 2007)
The article presents the many dilemmas concerning the status of English language-and-culture (as a conjoint phenomenon) and the approach to teach it in a non-native environment. It especially focuses on the alternatives of teaching English as a foreign or as an international language, pointing to the problems relating to the choice of any of these particular frameworks.